How do you multiply #(x-1)(x-2)(x-3)#?

Answer 1

#(x-1)(x-2)(x-3) = x^3-6x^2+11x-6#

It is helpful to know that:

#(x-alpha)(x-beta)(x-gamma)#
#= x^3-(alpha+beta+gamma)x^2+(alphabeta+betagamma+gammaalpha)x-alphabetagamma#
In this identity the expressions forming the coefficients of #x^k# are (apart from the alternating signs), the elementary symmetric polynomials in #alpha, beta, gamma#, namely:
#alpha+beta+gamma#
#alphabeta+betagamma+gammaalpha#
#alphabetagamma#
With #alpha=1#, #beta=2# and #gamma=3#, we find:
#alpha+beta+gamma=1+2+3=6#
#alphabeta+betagamma+gammaalpha=(1 * 2) + (2 * 3) + (3 * 1) = 2+6+3=11#
#alphabetagamma = 1 * 2 * 3 = 6#

So:

#(x-1)(x-2)(x-3) = x^3-6x^2+11x-6#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To multiply (x-1)(x-2)(x-3), you can use the distributive property and multiply the expressions two at a time, then simplify the result. Here's the step-by-step process:

  1. Multiply (x-1) by (x-2): (x-1)(x-2) = x(x) + x(-2) - 1(x) - 1(-2) = x^2 - 2x - x + 2 = x^2 - 3x + 2

  2. Now, multiply the result from step 1 by (x-3): (x^2 - 3x + 2)(x-3) = (x^2)(x) + (x^2)(-3) - (3x)(x) - (3x)(-3) + 2(x) + 2(-3) = x^3 - 3x^2 - 3x^2 + 9x - 3x + 9 + 2x - 6 = x^3 - 6x^2 + 8x - 6

So, (x-1)(x-2)(x-3) = x^3 - 6x^2 + 8x - 6.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7